2015
DOI: 10.1016/j.jconrel.2015.04.028
|View full text |Cite
|
Sign up to set email alerts
|

Disassembling bacterial extracellular matrix with DNase-coated nanoparticles to enhance antibiotic delivery in biofilm infections

Abstract: Infections caused by biofilm-forming bacteria are a major threat to hospitalized patients and the main cause of chronic obstructive pulmonary disease and cystic fibrosis. There is an urgent necessity for novel therapeutic approaches, since current antibiotic delivery fails to eliminate biofilm-protected bacteria. In this study, ciprofloxacin-loaded poly(lactic-co-glycolic acid) nanoparticles, which were functionalized with DNase I, were fabricated using a green-solvent based method and their antibiofilm activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
132
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(139 citation statements)
references
References 41 publications
7
132
0
Order By: Relevance
“…Once biofilm matrix with extra polymeric substances is in place, impermeable property inhibits the penetration of therapeutic agents. Nanoparticles are able to penetrate the biofilm owing to their nano-scale particle size [57, 58]. …”
Section: Discussionmentioning
confidence: 99%
“…Once biofilm matrix with extra polymeric substances is in place, impermeable property inhibits the penetration of therapeutic agents. Nanoparticles are able to penetrate the biofilm owing to their nano-scale particle size [57, 58]. …”
Section: Discussionmentioning
confidence: 99%
“…71 Ciproflaxin loaded poly(lactic-co-glycolic acid) nanoparticles modified with DNase I were investigated by Torrents and co-workers for the eradication of established biofilms. 63 While the particles were not able to prevent biofilm formation, from planktonic bacteria, they successfully reduced biofilm mass and size (Fig. 4A).…”
Section: Polymer Nanoparticles and Hydrogelsmentioning
confidence: 98%
“…Repeated administration over 3 days reduced 95% and eradicated more than 99.8% of established biofilms. 63 Polymeric nanofibers, composed of PLGA and PCL, were developed by Ashbaugher et al for local co-delivery of a combination of antibiotics. 80 The release can be adjusted by varying the PLGA/PCL polymer ratio and proved to be highly effective in preventing medical device infections in patients.…”
Section: Polymer Nanoparticles and Hydrogelsmentioning
confidence: 99%
“…The present study was similar to that of reported by Visha et al [23].The difference in the reported sizes of nanoparticles could be explained by the variation in the strain used as bacterial proteins play a major role in controlling the size and shape of nanoparticles .In the present study it was found that SeNPs was effective against biofilm forming carbohydrate content reduction by SeNPs was found to be in all microorganisms respectively. The small size of nanoparticles alone [25]or combined with antibiotic activity of metals [26] has been employed by other researchers as well for the disruption of extracellular matrix in microbial biofilms.…”
Section: Bacillus Subtilismentioning
confidence: 99%